2009
DOI: 10.2106/jbjs.h.00580
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cultural Factors on Outcome of Ponseti Treatment of Clubfeet in Rural America

Abstract: Compliance with the orthotic regimen after cast treatment is imperative for the Ponseti method to succeed. The striking difference in outcome in rural Native American patients as compared with the outcomes in urban Native American patients and children of other ethnicities suggests particular problems in communicating to families in this subpopulation the importance of bracing to maintain correction. An examination of communication styles suggested that these communication failures may be culturally related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
89
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 17 publications
8
89
2
3
Order By: Relevance
“…This correlation was found in Cape Town and Bali and Sumatra and confirms similar findings in Asia [18,20], Africa [15] and the Americas [14,21], where physical accessibility is described as a barrier for the Ponseti treatment as well. Specialized clubfoot clinics in rural areas are previously proven as a solution for overcoming this barrier [8,22].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This correlation was found in Cape Town and Bali and Sumatra and confirms similar findings in Asia [18,20], Africa [15] and the Americas [14,21], where physical accessibility is described as a barrier for the Ponseti treatment as well. Specialized clubfoot clinics in rural areas are previously proven as a solution for overcoming this barrier [8,22].…”
Section: Discussionsupporting
confidence: 86%
“…In Cape Town there was a shuttle service from the clinic to the closest train station (1.5 km uphill), which helped parents to access the clinic. The travel duration also has an influence on follow up; the likelihood of decreased compliance to the bracing protocol is greater when caregivers have to travel a long time to the hospital, resulting in higher relapse rates [14]. Especially in the low-and middle income setting, relapse means an extra heavy burden on the family and the healthcare system after all the investments in the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as initial disease severity, age of starting treatment, previous treatment, total casts required, tenotomy, gender, family history of clubfoot, and social status, which were suggested as possible influences were shown have no influence on recurrence [8,15,[17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Compliance with brace has been identified as the most important factor influencing recurrence [5,4,7,14,18,19,[21][22][23][24][25][26]. Morcuende et al reported in a study that noncompliant group had an 80% recurrence when compared to only 6% recurrence in compliant group.…”
Section: Discussionmentioning
confidence: 99%